Descriptive Analysis of Cervical Insufficiency in Primigravida: Insights into Cerclage Intervention and Clinical Impact - Ayesha Saddiqa; Afshan Ambreen; Sadaf Chughtai; Sadia Ghaffar; Muhammad Awais Qarni; Zaina Tahir; Pakeeza Shafique Ul Rehman (Pakistan Journal of Medicine and Dentistry)
Background: Cervical incompetence (CI) is a severe obstetric disorder that can result in pregnancy loss in the second trimester and preterm birth. Cervical cerclage is a routinely utilized method for treating CI, however its efficacy in primigravida individuals requires further investigation. This study aimed to find the frequency of cervical incompetence requiring cervical cerclage in patients entering their second trimester.